On the Characteristics of the Dynamic Waveform and the Change of Stress Wave Propagation Velocity in Soil Anchors - Zeng, Sheng; Zhang, Jing; Sun, Bing; Ma, Aiyang (Journal of Engineering and Technological Sciences, 2015)
This research used nondestructive testing technology to evaluate the anchorage quality of soil anchors. We first created a soil model in the laboratory and then performed a nondestructive experiment on the soil anchor using the stress wave reflection method. Our study displays variable characteristics of the acceleration response curve of a soil anchor under transient excitation. The fixed end reflection signal was very strong, while the reflected signal from the embedded end was weak. This is mainly caused by attenuation of both the fixed reflection signal and the stress wave. The stress wave velocity characteristics in the soil anchor were between the values of anchorage medium materials and free anchors. The velocity is not only related to the characteristics of the bolt body and anchorage medium, but also to the adhesive strength between the bolt and anchorage medium.